An Attempt of Employee Subduing in Corporate Sects - Kosenda, Aleksandra; Kukuła, Paulina (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article focuses on a blurred boundary of work and life balance in corporate structures. The first part contains theoretical basics for sects and a description of a corporate cult. The other part includes the results of empiric research in an international corporation functioning in IT area.